Programming Tools for Mathematics - Zohra Mahfouf (My University, 2025)
In the modern era, mathematics is no longer confined to paper and pencil—it thrives in the digital realm. For mathematics students, coding has become an essential skill that transforms abstract ideas into tangible solutions. The ability to design algorithms, manipulate data, and visualize complex phenomena opens doors to deeper understanding and creativity, allowing students to explore the beauty and power of mathematics in ways that were previously unimaginable. Programming is not just a tool; it is a bridge between theory and practice, empowering students to experiment, innovate, and solve real-world problems with precision and insight. This course is designed to provide students with a comprehensive foundation in scientific programming, equipping them with both the theoretical knowledge and practical skills necessary for modern computational work. Beginning with the essentials, students learn to set up programming environments, handle variables, and use basic functions effectively. They then explore numbers—natural, real, and complex—laying the groundwork for precise numerical computation. Building on these fundamentals, students master vectors and matrices, unlocking the ability to model and analyze multidimensional data. The course progresses to core programming elements such as scripts, functions, loops, and conditional statements, guiding students to write efficient, structured, and reusable code. Students also engage with polynomials, graphical representations of 2D and 3D curves, function graphs, and analytical surfaces, developing both analytical and visual understanding. The curriculum culminates with symbolic computation, covering tasks such as expansion, factorization, differentiation, integration, limits, and series expansions, allowing students to tackle a wide range of mathematical problems with confidence. Throughout the course, practical exercises using Matlab (licensed) or Scilab reinforce theoretical concepts and build hands-on experience. By the end, students are not only proficient in programming tools but also equipped with the creativity, rigor, and curiosity needed to apply these skills in advanced studies, research, and professional fields where mathematics and computation intersect. This course invites students to embrace rogramming as a powerful companion to mathematical thought—a journey of discovery where logic, creativity, and technology come together to transform knowledge into action.
Keywords: Matlab; Coding tools for Mathemathics; Scilab